World revision of Iteaphila macquarti group (Diptera: Empididae) - Sinclair, Bradley J.; Shamshev, Igor V. (Zootaxa, 2012)
Nineteen species are recognized in the Iteaphila macquarti group, including ten new species (I. bulbosa Sinclair sp.nov. (British Columbia, Canada), I. californica Sinclair sp. nov. (Baja California, Mexico), I. chvalai Shamshev sp.nov. (Kazakhstan), I. cirrata Shamshev sp. nov. (British Columbia, Canada), I. falcata Sinclair sp. nov. (BritishColumbia, Canada), I. furcata (Zetterstedt), I. macquarti Zetterstedt, I. napaea Melander, I. nepalensis Shamshev sp.nov. (Nepal), I. nitidula Zetterstedt, I. orchestris Melander, I. pumila Sinclair sp. nov. (Alaska, USA), I. rasnitsyniShamshev sp. nov. (south Primorsk Territory, Russia), I. saigusai Shamshev sp. nov. (Nagano, Japan), I. sicamousSinclair sp. nov. (British Columbia, Canada), I. taiwanensis Shamshev sp. nov. (Taiwan), I. testacea Melander, I.triangula (Coquillett), I. vetula Melander). Iteaphila maackii Loew is considered a nomen dubium due to loss ofholotype. Empis luctosa Kirby is considered also a nomen dubium and proposed as a doubtful species of Iteaphila. Thefollowing new synonyms are proposed: (Empis cormus Walker, I. cana Melander, I. fulginosa Melander) = I.macquarti; (Hilara carbonella Zetterstedt, Empis conjuncta Coquillett) = I. nitidula. Lectotypes are designated for I.furcata, I. cana, I. carbonella (Zetterstedt), I. conjuncta, I. orchestris, I. testacea and I. triangula. The male of I.testacea is described for the first time, keys to Palearctic and Nearctic faunas are provided, and species are sorted intofive monophyletic subgroups. The distributions of all species are mapped and five Holarctic species are identified (I.cirrata, I. macquarti, I. nitidula, I. orchestris, I. pumila). Iteaphila is recorded for the first time from the OrientalRegion. Feeding habits for adult Iteaphila are summarized and reviewed, and the genus appears to be exclusively anthophilous (pollen feeding) and never predaceous.